2006
DOI: 10.1016/j.ijfatigue.2005.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of environmental effects on fatigue crack growth behaviour of a high strength steel in a saline solution with cathodic protection

Abstract: International audienceCrack growth rates of small fatigue cracks in a high strength steel tested in 3.5% NaCl solution with cathodic protection are analysed in the Paris regime through the comparison with the corresponding results obtained in air or in high vacuum. Environmental effects in the saline solution are due to hydrogen produced by cathodic polarisation, which causes intergranular and transgranular brittle fracture surfaces. By comparison to fatigue crack growth rates obtained in air, it could be conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 15 publications
(30 reference statements)
1
18
0
1
Order By: Relevance
“…Similarly, mechanical effects dominate and the crack is believed to advance as a faster rate than the diffusion of hydrogen in steel at high values of K [22,36,41]. In intermediate K regime, the increase in FCP rates for steels in seawater under CP potentials has been reported compared to an air environment, due to the effect of hydrogen within and immediately ahead of the crack tip plastic zone [22,42,43]. The present study indicated that the CP potentials of -850 and -1,050 mV SCE suppressed the environmental effect of seawater on the FCP behavior of X80 steel over the entire K regime.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, mechanical effects dominate and the crack is believed to advance as a faster rate than the diffusion of hydrogen in steel at high values of K [22,36,41]. In intermediate K regime, the increase in FCP rates for steels in seawater under CP potentials has been reported compared to an air environment, due to the effect of hydrogen within and immediately ahead of the crack tip plastic zone [22,42,43]. The present study indicated that the CP potentials of -850 and -1,050 mV SCE suppressed the environmental effect of seawater on the FCP behavior of X80 steel over the entire K regime.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the test results of high-strength steel wires, Huneau and Mendez (2006) suggested us to evaluate corrosion fatigue crack growth using Paris-Erdogan law (Paris & Erdogan, 1963):…”
Section: Corrosion Fatiguementioning
confidence: 99%
“…The crack growth rate due to corrosion fatigue often consists of three regions depending on the amplitude of stress intensity factor Δ K , and each region is generally modeled by a power law defined by Equation (8) 26. In the first region, the crack growth rate due to corrosion fatigue is higher than that in air; the second region is associated with a frequency‐dependent plateau that implies a nearly constant crack growth rate; while in the third region the crack growth rate is similar to that in air.…”
Section: Deterioration Process Of Suspender Under Traffic Loadsmentioning
confidence: 99%
“…In the first region, the crack growth rate due to corrosion fatigue is higher than that in air; the second region is associated with a frequency‐dependent plateau that implies a nearly constant crack growth rate; while in the third region the crack growth rate is similar to that in air. However, Huneau and Mondez 26 conducted corrosion fatigue tests of high‐strength steel wires with a diameter of 5 mm in 3.5% NaCl solution, and measured crack growth rates of small cracks. Different power‐law regions were not observed in their testing results, because the crack growth rates remain below the value corresponding to the plateau observed in long crack d a /d N –Δ K curves 26.…”
Section: Deterioration Process Of Suspender Under Traffic Loadsmentioning
confidence: 99%